تقييم تعلم اللغة العربية باستخدام منصة استوديو البيانات من جوجل، وقوة ذكاء الأعمال، وجدول الذكاء الاصطناعي، وبيثون للذكاء الاصطناعي في المدرسة المتوسطة طيّب هاشم بجورونغان بروبولينغو - rofiqsofa, Ainur Rofiq Sofa (Insya : Journal of Arabic Studies, 2025)
This study explores the effectiveness of Arabic language instruction at MTs Thoyyib Hasyim Jorongan Probolinggo through the application of modern digital technologies, including Google Data Studio, Power BI, Table AI, and Python AI. Employing a descriptive-analytical method, data were gathered via classroom observations, surveys, and interviews with both teachers and students. The collected information was then processed using AI-driven analytical tools. The findings suggest that integrating digital tools significantly enhances the accuracy, efficiency, and speed of evaluating the learning process. Additionally, these technologies provide data-informed insights that support the improvement of Arabic language education. Based on these outcomes, the study recommends the broader adoption of digital innovation within the educational system, particularly in language learning.